2005
DOI: 10.1016/j.virol.2005.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Induction and mode of action of the viral stress-inducible murine proteins, P56 and P54

Abstract: Mammalian cells respond to virus infection or other viral stresses, such as double-stranded (ds) RNA and interferons (IFN), by robust and rapid induction of viral stress-inducible proteins. The induction and actions of one such protein, the human P56, have been extensively studied. However, little is known about the distantly related mouse proteins, MuP56 and MuP54. Here, we report that, in mouse cells, they could be induced by IFN, dsRNA or Sendai virus infection. MuP56 and MuP54 inhibited protein synthesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
72
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 50 publications
7
72
1
Order By: Relevance
“…32,33 The function of I-8U is unknown, but ISG54 may be involved in translation control. 34 Two of the IRF-3-dependent genes confer resistance to specific infectious agents; cytomegalovirus-induced gene 5 (cig5)/viperin blocks late cytomegalovirus gene expression and virion production, and the GTPase LRG-47 serves to protect macrophages against infection by Mycobacterium tuberculosis independent of inducible nitric oxide synthetase. [35][36][37] IRF-3 action has been linked to apoptosis and for this reason target genes that affect cell death or survival were examined.…”
Section: Irf-3 Target Genesmentioning
confidence: 99%
“…32,33 The function of I-8U is unknown, but ISG54 may be involved in translation control. 34 Two of the IRF-3-dependent genes confer resistance to specific infectious agents; cytomegalovirus-induced gene 5 (cig5)/viperin blocks late cytomegalovirus gene expression and virion production, and the GTPase LRG-47 serves to protect macrophages against infection by Mycobacterium tuberculosis independent of inducible nitric oxide synthetase. [35][36][37] IRF-3 action has been linked to apoptosis and for this reason target genes that affect cell death or survival were examined.…”
Section: Irf-3 Target Genesmentioning
confidence: 99%
“…It is estimated that more than 300 genes are responsive to IFN by oligonucleotide arrays (Der et al, 1998), and some ISGs including Mx, dsRNA-dependent protein kinase R (PKR), 2 ,5 -oligoadenylate synthetase (2-5 OAS)/RNase L and RNAspecific adenosine deaminase (ADAR) have been well characterized for their ability to affect virus replication, transcription or cell growth, while the exact biochemical and cellular functions of most ISGs remain unknown (Samuel, 2001). Recent studies have shown that other ISGs including IFI54 (Terenzi et al, 2005), Viperin (Chin and Cresswell, 2001), ISG20 (Espert et al, 2003), ISG15 (Lenschow et al, 2005) also confer resistance to virus invasion, suggesting the existence of additional ISG-mediated pathways involved in IFN antiviral response.…”
Section: Introductionmentioning
confidence: 99%
“…Secreted IFNs then participate in an autocrine/ paracrine loop by the JAK-STAT pathway that transmits the signal to the nucleus, and results in the expression of a set of ISGs, such as Mx, dsRNAdependent protein kinase R (PKR) and 2-5 oligo(A) synthetase (2-5 OAS) to inhibit virus replication in host cells [1]. Recent studies showed that other ISGs, including IFI56 [9], IFI54 [10], Viperin (virus inhibitory protein, endoplasmic reticulum-associated, interferon-inducible) [11], ISG20 [12], ISG15 [13] and RNA-specific adenosine deaminase (ADAR) [1] also contribute to limit virus replication and spread.…”
Section: Introductionmentioning
confidence: 99%